2005
DOI: 10.1159/000085384
|View full text |Cite
|
Sign up to set email alerts
|

Search for Natural Products Related to Regeneration of the Neuronal Network

Abstract: The reconstruction of neuronal networks in the damaged brain is necessary for the therapeutic treatment of neurodegenerative diseases. We have screened the neurite outgrowth activity of herbal drugs, and identified several active constituents. In each compound, neurite outgrowth activity was investigated under amyloid-β-induced neuritic atrophy. Most of the compounds with neurite regenerative activity also demonstrated memory improvement activity in Alzheimer’s disease-model mice. Protopanaxadiol-type saponins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
133
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(142 citation statements)
references
References 43 publications
2
133
0
7
Order By: Relevance
“…Such atrophy leads to the destruction of neuronal networks, and subsequently to the fatal dysfunction of brain systems. TGN has been shown to cause neurite outgrowth with human neuroblastoma SK-N-SH cells (Mattila et al, 1999) and induce neuronal regeneration (Tohda et al, 2005) in vitro. TGN-induced neurite outgrowth might have enhanced functional connectivity of neurons and helped to preserve synaptic connectivity in MPTP-induced mice in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such atrophy leads to the destruction of neuronal networks, and subsequently to the fatal dysfunction of brain systems. TGN has been shown to cause neurite outgrowth with human neuroblastoma SK-N-SH cells (Mattila et al, 1999) and induce neuronal regeneration (Tohda et al, 2005) in vitro. TGN-induced neurite outgrowth might have enhanced functional connectivity of neurons and helped to preserve synaptic connectivity in MPTP-induced mice in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TGN has potential to prevent the progression of PD by exclusion of, or at least a decrease in the magnitude of, neuronal atrophy. The ability of TGN to induce neurite outgrowth and regeneration indicated the potential to protect vital organs against oxidative stress (Mattila et al, 1999;Tohda et al, 2005). TGN is a potent antioxidant Figure 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several withanolides isolated from the methanolic extract of W. somnifera roots as well as the extract itself, have been shown to possess neurite outgrowth activity (21,261). Withanoside IV (31) and VI (32) predominantly induced dendritic outgrowth in normal cortical neurons, while withanolide A (504) predominantly induced axon outgrowth (262).…”
Section: Synaptogenesis and Neuritic Outgrowthmentioning
confidence: 99%
“…Its seeds and leaves are used for food and also in traditional medicine (Sharma et al, 1996;Warrior and Nambiar, 1995). Some studies reported that trigonelline, a compound isolated from fenugreek, exhibited nerve regeneration and improved memorial activity in AD-induced mice (Tohda et al, 2005). Therefore, in India prepared bread from fenugreek seeds, wheat and maize is used for general population as protection against several diseases including AD.…”
Section: Introductionmentioning
confidence: 99%